Kingdom of the Netherlands-Curacao and Sint Maarten : 2021 Article IV Consultation Discussions; Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic inflicted another major shock on the economies of Curacao and Sint Maarten, which followed category 5 hurricanes in Sint Maarten in 2017 and the spillovers of the Venezuelan crisis on Curacao. Despite the substantial response measures financed by The Netherlands, the economic contraction in 2020 was severe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Curacao, Kingdom of the Netherlands